Evaluation of the serum fasting insulin and HOMA-IR in diabetic and FDR patients - Dipalee Rahul Navale; Vaishali Shashil Patil (Journal of Clinical and Basic Research)
Background: Diabetes mellitus is an endocrine disorder. It is one of the leading causes of morbidity and mortality due to its role in the development of microvascular and macrovascular complications. The main pathophysiological features of type 2 diabetes mellitus are impaired insulin secretion and increased insulin resistance (IR). There is a relationship between fasting serum insulin, IR, and beta-cell dysfunction. Familial aggregation is a significant risk factor for early-onset type 2 diabetes mellitus. First-degree relatives not only share genetic predispositions but also socio-environmental risk factors like obesity and hyperglycemia, forming a high-risk group. Methods: The study population consists of 60 people, including healthy controls (n = 20), first-degree relatives (n = 20), and diabetes patients (n = 20). The level of serum fasting insulin was measured by the chemiluminescence immunoassay method. IR was calculated using mathematical formulas such as HOMA-IR and HOMA-B. Results: The results showed that the level of serum insulin increased in the FDR group (8.5 ± 5.6) compared to the diabetic and control groups (p < 0.001). HOMA-IR was significantly increased in individuals with diabetes (2.10 ± 1.10) and the FDR group (1.81 ± 1.25) compared to controls (p < 0.0001). We also noted a strong positive correlation between fasting serum insulin and HOMA-IR in the FDR group (r = +0.98) and in diabetic patients (r = +0.79). Conclusion: Serum fasting insulin is an excellent and dependable marker for diagnosing IR in individuals at risk of developing diabetes, including FDR.